Экспериментальная проверка качества товарного триэтилалюминия в полимеризации пропилена - Трофимова А. С.; Аркатов О. Л.; Мубаракшин Р. Р.; Барнягина О. В.; Майер Э. А. Эдуард Александрович (2011, 2011)
Заглавие с экрана